Reinventing the Good Life An empirical contribution to the philosophy of care - Pols, Jeannette (UCL Press, 2023)
Ever since Adam Smith's musings on 'the invisible hand' became more famous than his work on moral sentiments, social theorists have paid less attention to everyday ethics and aesthetics. Smith's metaphor of the invisible hand posits that social outcomes emerge by dint of the behaviours of individuals rather than their intentions or virtues. Modernist and scientific approaches to determining the common good or good forms of governance have increasingly relied on techniques of generalisation and rationalisation. This shift has meant that we no longer comprehend why and how people display a deep concern for everyday life values in their social practices. People continue to enact these values and live by them while academics lack the vocabulary and methods to grasp them. By reconstructing the history of ideas about everyday-life values, and by analysing the role of such values in contemporary care practices for patients with chronic disease in the Netherlands, Reinventing the Good Life explores new ways to study the values of everyday life, particularly in situations where the achievement of a clear cut or uniform good is unlikely. The book presents a practice-based epistemology and methodology for studying everyday care practices and supporting their goodness. This analytical approach ultimately aims to generate ideas that will allow us to relate in more imaginative ways to the many pressing concerns that we are forced to live with today.